Analysis of the antimicrobial activity of local anaesthetics used for dental analgesia - Pelz, Klaus; Wiedmann-Al-Ahmad, Margit; Bogdan, Christian; Otten, Jörg Elard (Journal of Medical Microbiology, 2008)
Seven local anaesthetics and their active anaesthetic components [Ultracaine D-S (articaine hydrochloride), Carbostesin (bupivacaine hydrochloride), Scandicaine (mepivacaine hydrochloride), Xylonest (prilocaine hydrochloride), Xylocaine (lidocaine hydrochloride), Hostacaine (butanilicaine phosphate) and Novocaine (procaine hydrochloride)] were tested for their antimicrobial activity against 311 bacterial strains from 52 different species and 14 Candida albicans strains. The tested pathogens were members of the oral flora, and partly members of the skin and intestinal flora. Additionally, the antimicrobial activity of methyl-4-hydroxybenzoate, sodium disulfite, adrenaline hydrogen tartrate and adrenaline (the preservative and vasoconstrictive components of the anaesthetics) was tested. For determination of MIC and minimal bactericidal concentration (MBC), the agar dilution method using Wilkins-Chalgren agar was applied. The trade preparation Ultracaine D-S showed the most prominent antimicrobial activity with regard to both MIC and MBC. Ultracaine D-S and its active substance, articaine hydrochloride, showed similar MIC values, suggesting that the antimicrobial activity is mainly caused by the anaesthetic component. Novocaine showed the lowest antimicrobial activity and did not inhibit 35 of the species tested. The MIC values of all local anaesthetics were between 0.25 and 16 mg ml-1. The routinely applied concentration of Ultracaine D-S was roughly four times higher, and of Hostacaine was two times higher, than the MBC values for the tested bacteria, whereas for the other anaesthetics, the MBC values were not reached or exceeded with the concentrations used. The MIC range of the preservatives was 0.5-1.0 mg ml -1 for methyl-4-hydroxybenzoate and 0.2-0.5 mg ml-1 for sodium disulfite. The articaine MIC values were two to three serial dilution steps lower, and the butanilicaine MIC values one to two serial dilution steps lower, than the MIC of the preservatives. The mepivacaine mean MIC values were slightly lower for Fusobacterium nucleatum, Prevotella intermedia, Porphyromonas gingivalis and Staphylococcus aureus, but higher for Streptococcus intermedius, compared with the preservative methyl-4-hydroxybenzoate. The same result was found with Streptococcus intermedius and lidocaine. Screening of 20 MIC values of 4 pure anaesthetic substances and the corresponding preservative found 2/20 instances where the MICs of the preservatives against 5 representative species (67 strains) were lower, indicating that the antimicrobial effect was mainly due to the preservative, but 18/20 results where the pure anaesthetic component showed greater antimicrobial effects compared with the preservative. The in vitro results for Carbostesin, Scandicaine and especially for Novocaine indicate that a local disinfection should be done prior to injection of the anaesthetics. Due to the results obtained with nosocomial strains (Escherichia coli, S. aureus and Pseudomonas), disinfection of the mucous membranes should be performed routinely in immunocompromised patients, regardless of the anaesthetic used. © 2008 SGM.
CRIS-Team Scopus Importer:2024-02-26